Effect of dry ice application in fish hold of fishing boat on the fish quality and fisherman income - Semin, Semin; Baheramsyah, Alam; Amiadji, Amiadji; Abdul Rahim, Ismail (Science Publications, 2011)
Problem statement: This study presents the effect of dry ice application in the fish hold of fishing boat on the fish quality and fisherman income. Dry ice is made with compressed CO2 gas to produce hot, high-pressure gas. Hot gas then cooled to condense into liquid CO2, which is still high pressure. Dry ice can be used to cool a room and can reach temperatures under 0°C. Approach: Objectives of this study are to know the effect of the use of cooling applications by using dry ice as a cooling fish on the fish quality. Results: The experimental investigation has been done in dry ice variations weigh, variations cooling load (fish) and variations fan speed. Conclusion: The results of these experiments have been shown in this study that the dry ice has been reducing the weight of refrigerant weigh to cooling of fish in the fishing boat.